2012
DOI: 10.4236/jep.2012.312184
|View full text |Cite
|
Sign up to set email alerts
|

Elements Content in Otolith as Pollution Indicator for Cultured Sea Bass (Lates calcarifer) of Malaysia

Abstract: Otoliths of cultured sea bass and ambient waters were sampled from 24 fish cages and ponds in Malaysia to investigate the contents of Sr, Mg, Ba, Cd and Zn. The following elements content in otolith and water were analysed with Inductively Coupled Plasma Mass Spectrometer (ICP-MS) and/or Atomic Absorption Spectrometer (AAS) to determine the anthropogenic impacts based on the grouping characterisation of the sampling locations. Three groups i.e. A, B and C were characterised according to the least, intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the laboratory, the water sample was filtered using pre-weighed glass fibre filter paper (D = 47 mm, Φ = 0.45 mm) and dried until constant weight. Filter paper containing TSS was digested with mixture of 10 mL of nitric acid (HNO 3 ), 5 mL of perchloric acid (HClO 4 ) and 1 mL of hydrofluoric acid (HF) for 2 h in Teflon beaker at 120°C (Daud et al 2013;Sarimin & Mohamed 2012;Yusoff et al 2015). The concentrations of chromium and gallium were determined using the Inductively Coupled Plasma Mass Spectrometry (ICP-MS).…”
Section: Methodsmentioning
confidence: 99%
“…In the laboratory, the water sample was filtered using pre-weighed glass fibre filter paper (D = 47 mm, Φ = 0.45 mm) and dried until constant weight. Filter paper containing TSS was digested with mixture of 10 mL of nitric acid (HNO 3 ), 5 mL of perchloric acid (HClO 4 ) and 1 mL of hydrofluoric acid (HF) for 2 h in Teflon beaker at 120°C (Daud et al 2013;Sarimin & Mohamed 2012;Yusoff et al 2015). The concentrations of chromium and gallium were determined using the Inductively Coupled Plasma Mass Spectrometry (ICP-MS).…”
Section: Methodsmentioning
confidence: 99%
“…Our results show that Zn/Ca ratio is the only element with a higher value in otoliths from Trappeto's farm. Zn concentration in otoliths appears to be related to pollution from terrestrial areas (Sarimin and Mohamed 2012). In the Castellammare Gulf, the coastal waters are impacted by industrial discharges coming from a distillery located on the Piana of Partinico, and as reported by different studies, this kind of industrial waste is contaminated by heavy metals such as Cr, Ni, and Zn (Pandey et al 2008;Kannan and Upreti 2008).…”
Section: Trace Element Distribution In Otolithsmentioning
confidence: 97%
“…Particularly, total length (TL), standard length (SL), and total weight (TW) were measured by using a balance and an ichtiometer, respectively (Table 1). Fish head were cut horizontally parallel to the preopercle in order to expose the sagittal otolith (Sarimin and Mohamed 2012). The right sagitta was extracted from sea bass specimens using plastic forceps and cleaned with deionized water.…”
Section: Study Areas and Sampling Collectionmentioning
confidence: 99%
See 1 more Smart Citation